Daytime napping is associated with retinal microcirculation: a large population-based study in China. Issue 3 (20th November 2021) - Liu, Xin; Wang, Guowei; Wang, Xiaoyan; Wang, Yueye; Min, Yan; Zhang, Janice; Chang, Robert T; Zhao, Xueyin; He, Wei; Moshfeghi, Darius M; Lu, Ying; Hsing, Ann W; et al.
Abstract: Study Objectives: To investigate the association between daytime napping and retinal microcirculation. Methods: This is a cross-sectional study from a prospective population-based cohort. 2, 662 participants were recruited after quota sampling. Information on napping was collected through face-to-face interviews. Retinal vascular calibers (RVCs), including central retinal arteriolar equivalent (CRAE), central retinal venular equivalent (CRVE), and arterio-to-venous ratio (AVR), were obtained from fundus photography. Multivariate regression and restricted cubic spline curve were performed to determine the association between RVCs and daytime napping duration. Results: 56.4% participants reported daytime napping regularly. Compared to no nap, daytime nap was related to higher CRAE, with nap duration of 0.5–1 h showing the most significant association. 0.5–1 h daytime nappers displayed an average of 4.18 µm (95% confidence interval [CI] 2.45–5.91, p < 0.001) wider CRAE than non-nappers after adjustment. No significant association was found between CRVE and daytime napping. Moreover, individuals with 0.5–1 h daytime napping had a lower risk for AVR reduction (odds ratio [OR] 0.70, 95% confidence interval [CI] 0.56–0.86, p = 0.001) than non-nappers. Similar association persisted in non-hypertensive population. Restricted cubic spline indicated a J-shaped relationship between AVR reduction and nap duration. Conclusion: Retinal microcirculation was positively associated with self-reported 0.5–1 h daytime napping. Better indicators of retinal microcirculation were probably related to nap duration in a J-shaped manner. Also, the possibly beneficial role of 0.5–1 h daytime napping on retinal microcirculation might be independent of clinically diagnosed vascular diseases.